Research exploration and learning practices for prospective mathematics teachers - Ilham, Adjie Muhamad; Umam, Khoerul (International Journal of Trends in Mathematics Education Research, 2023)
In the world of education, a study has quite a large influence on education practitioners. This study aims to analyze the relationship between research and learning practices for prospective mathematics teachers. In this context, researchers will explore the understanding of prospective mathematics teachers on existing research related to the practice of teaching mathematics prospective teachers. The research method used in this study is a quantitative research method with the type of research used in this research is correlational. The results of this study are in line with the research objectives, namely wanting to see whether there is an influence on research with learning practices for prospective mathematics teachers. The data shows that there is an influence between research on learning practices for prospective mathematics teachers.